Kajian Gejala Penyearahan Optik pada Metamaterial Chiral - Juliasih Partini; Kamsul Abraha; Arief Hermanto; Satoshi Tomita; Matsui Takahiro (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Chiral metamaterial is a new breakthrough in the fabrication of a metamaterial because of the capability of providing different refractive index values for each circular polarization angle. This provides opportunities to obtain negative refractive index values, without the necessity to have simultaneously negative values for both permittivity and permeability. This study investigated the optical rectification, which is the phenomenon of second order non-linear optics in the chiral metamaterial. This relates to the testing of the new designs of square structure chiral metamaterial. Optical rectification is often used to 'rectify' femtoseconds laser from the realm of visible light into the terahertz domain. Nonlinear response of metamaterial was observed by terahertz emission spectroscopy. The results showed that the obtained terahertz signal is proportional to the square of the laser power used. This suggests that in theincoherent optical rectification, there is a mixture of optical rectification with the second harmonic wave generation. Development of square-structured chiral metamaterials is expected to be an alternative source of material due to the lack of non-linear material that can be used in the terahertz domain.